Implanted injection port for routine drug delivery to the middle ear in mice - Isabel T. Held; Niranj A. Kumar; Azmi Marouf; Kumar N. Alagramam (PLoS ONE, 2026)
Small molecule drugs designed to rescue disorder-specific mutant proteins causative of progressive sensorineural hearing loss need to be delivered regularly. An example is clarin-1 N48K in Usher syndrome type IIIA (USH3A). In these cases, local delivery has significant advantages over systemic delivery. Genetic predisposition to sensorineural hearing loss may mean the invasive (surgical) approach to access the cochlea is detrimental to hearing preservation. Alternatively, delivering drugs near the round and oval window from the middle ear or tympanic cavity via a tympanostomy tube may be a viable option to treat genetic hearing loss. To test the hypothesis in a mouse model, we first must develop a way to routinely deliver the drugs to the tympanic cavity space in mice that is minimally detrimental to hearing and translatable to humans. Limitations of size and other practical considerations preclude implantation of a tympanostomy tube in mice. The goal of this pilot study was to determine feasibility and assess the impact of implanting an injection port in mice. This approach would serve as a surrogate for drug delivery through tympanostomy tubes in humans. We repurposed the Vascular Access Button (Instech Labs, PA) to access the tympanic cavity in mice that mimics hearing loss in USH3A and its wild-type counterpart. The right ear served as the non-surgical control for all mice. At 2- and 4-weeks post-operation, we monitored behavior, physical attributes, balance, and hearing. The implant was generally well-tolerated in mice. Saline injections through the port were tested for two weeks post-operation without issue, and hearing was not significantly affected. Here, we present a fully implantable method in mice for routine drug delivery to the middle ear, with minimal damage or implant-induced hearing loss. This approach could be used to investigate drug therapies in preclinical models of sensorineural hearing loss.